Spatio‐Temporal Parameters of Endosomal Signaling in Cancer: Implications for New Treatment Options. Issue 4 (16th November 2015) - Stasyk, Taras; Huber, Lukas A.
ABSTRACT: The endo/lysosomal system in cells provides membranous platforms to assemble specific signaling complexes and to terminate signal transduction, thus, is essential for physiological signaling. Endocytic organelles can significantly extend signaling of activated cell surface receptors, and may additionally provide distinct locations for the generation of specific signaling outputs. Failures of regulation at different levels of endocytosis, recycling, degradation as well as aberrations in specific endo/lysosomal signaling pathways, such as mTORC1, might lead to different diseases including cancer. Therefore, a better understanding of spatio‐temporal compartmentalization of sub‐cellular signaling might provide an opportunity to interfere with aberrant signal transduction in pathological processes by novel combinatorial therapeutic approaches. J. Cell. Biochem. 117: 836–843, 2016. © 2015 The Authors. Journal of Cellular Biochemistry Published by Wiley Periodicals Inc.